The use of assessment for learning in Physical Education classes: preservice teachers’ perceptions (Revista Infancia, Educación y Aprendizaje, 2019)
Assessment is not a consensual topic among teachers, and several are the challenges it poses, especially to those in training. Among the different assessment perspectives, the use of it as a means of promoting learning has been gaining ground. This paper aims to capture the understandings, advantages, and problems that preservice teachers faced during the implementation of Assessment for Learning (AfL) in Physical Education classes during their school placement. Semi-structured interviews were carried out with four preservice teachers, chosen to participate in this study. Using a thematic analysis, three categories were defined: 1) understanding about AfL; 2) experience of preparing and implementing AfL, and 3) impact of this experience on their future as a teacher. Preservice teachers seem to have a similar understanding of AfL. They reported that planning is demanding but impacted positively on students’ motivation and participation. This experience changed their way of preparing classes to a student-centered approach.